PENGARUH ABSENSI DIGITAL, INSENTIF, KEPUASAN KERJA TERHADAP KINERJA ASN DI PUSKESMAS PUSKESMAS KENJERAN, GUNUNGANYAR, DAN SAWAHAN, KOTA SURABAYA - Winda Winastuti; Sulistiyanto Sulistiyanto; Arfah Arfah (STKIP Pesisir Selatan, 2026)
Objective: This study aims to analyze the effects of digital attendance, incentives, and job satisfaction on employee performance, at several Public health centers (Puskesmas) in Surabaya, that implement digital attendance system and incentives to enhance civil servant performance. Methods: Using a quantitative with survey approach with a saturated sampling technique based on inclusion criteria, resulting in 111 respondents. Data were collected through closed-ended questionnaires and analyzed using multiple linear regression. Results: The partial (t-test) results indicate that digital attendance and job satisfaction have a positive and significant effect on performance (Sig. < 0,05), while incentives do not have a significant effect (Sig. > 0,05). Simultaneously (F-test), these variables explain 69.4% of the variance in employee performance. These findings underscore the importance of optimizing digital attendance systems and enhancing job satisfaction, as well as evaluating incentive policies to be more performance-based for sustainable performance improvement. Novelty: Prior studies examining the effects of digital attendance, incentives, and job satisfaction on employee performance have produced inconsistent results, necessitating further investigation by incorporating job satisfaction as a psychological variable that may influence performance.